Comparing High Lob and Roll Pointing in South Sulawesi Petanque Athletes - Hudain, Muh. Adnan; Ishak, Muhammad; Kasmad, Muhammad Rachmat; Pawarrangan, Albert; Juhanis, Juhanis (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
This study aims to determine the comparison of high lob and roll pointing techniques among South Sulawesi Petanque athletes at distances of 6, 7, 8, and 9 meters. This study employs a quantitative research design with a descriptive approach. Data collection techniques include observation, pointing skills tests, and documentation. At a distance of 6 meters, the research yielded results. The Mann-Whitney test yielded a result of 0.080, surpassing the significance level of 0.05. This result led to the acceptance of H0, indicating that the athletes' abilities did not differ between the pointing high lob and pointing roll techniques. At a distance of 7 meters, the Mann-Whitney test yielded a result of 0.508, surpassing the 0.05 level, indicating that the athletes' abilities do not differ between the Pointing High Lob and Pointing Roll techniques. At a distance of 8 meters, the result of the Mann-Whitney test is 0.817, which is a value greater than the 0.05 level, so at this distance, there is no comparison of athletes' ability to throw using the Pointing High Lob and Pointing Roll techniques. At a distance of 9 meters, the result of the Mann-Whitney test is 0.000, which is a value smaller than the 0.05 level, so at this distance, there is a comparison of athletes' throwing abilities between using the Pointing High Lob and Pointing Roll techniques.